Planktonic protist diversity across contrasting Subtropical and Subantarctic waters of the southwest Pacific. (August 2022) - Gutiérrez-Rodríguez, Andres; Lopes dos Santos, Adriana; Safi, Karl; Probert, Ian; Not, Fabrice; Fernández, Denise; Gourvil, Priscillia; Bilewitch, Jaret; Hulston, Debbie; Pinkerton, Matt; Nodder, Scott D.
Abstract: Planktonic protists are an essential component of marine pelagic ecosystems where they mediate important trophic and biogeochemical functions. Although these functions are largely influenced by their taxonomic affiliation, the composition and spatial variability of planktonic protist communities remain poorly characterized in vast areas of the ocean. Here, we investigated the diversity of these communities in contrasting oceanographic conditions of the southwest Pacific (33–58 °S) using DNA metabarcoding of the 18S rRNA gene. Seawater samples collected during twelve cruises ( n = 482, 0–3100 m) conducted east of New Zealand were used to characterize protist communities in Subtropical (STW) and Subantarctic (SAW) surface water masses and the Subtropical Front (STF) that separates them. Diversity decreased with increasing latitude and increasing temperature but tended to be lowest in the STF. Sample ordination resulting from the abundance of amplicon single variants (ASVs) corresponded to the different water masses. Overall, Dinoflagellata (Syndiniales, 27%; Dinophyceae, 24% of standardized number of reads) dominated the euphotic zone followed by Chlorophyta (20%), but their relative abundance and composition at class and lower taxonomic levels varied consistently between water masses. Among Chlorophyta, several picoplanktonic algae species of the Mamiellophyceae class including Ostreococcus lucimarinus dominated in STW, while the Chloropicophyceae species Chloroparvula pacifica was most abundant in SAW. Bacillariophyta (5%), Prymnesiophyceae (5%), and Pelagophyceae (2%) classes were less abundant but showed analogous water mass specificity at class and finer taxonomic levels. Protist community composition in the STF had mixed characteristics and showed regional differences with the southern STF (50 °S) having more resemblance with subantarctic communities than the STF over the Chatham Rise region (42–44 °S). Below the euphotic zone, Syndiniales sequences (40%) dominated the dataset followed by Radiolaria (31%), Dinophyceae (14%) and other heterotrophic groups like Marine Stramenopiles and ciliates (1–1.5%). Among Radiolaria, several unidentified ASVs assigned to Spumellaria were most abundant, but showed significantly different distributions between STW and SAW highlighting the need to further investigate the taxonomy and ecology of this group. The present study represents a significant step forward towards characterizing protistan communities composition in relation to major physical oceanographic features in the southwest Pacific providing new insights about the biogeography and ecological preferences of different planktonic protist taxa from class to species and genotypic level. Highlights: Water-mass preference of different taxa at class, species and genotypic levels. Mamiellophyceae green algae dominated in subtropical waters. Dinophyceae and Chloropicophyceae green algae dominated in subantarctic waters. A diverse assemblage of Radiolaria dominated the mesopelagic zone. Small rather than large taxa dominated phytoplankton blooms in subtropical waters.